Cluster Analysis of Earthquake’s Data Clustering in Indonesia using Fuzzy K-means Clustering - Ahmad, Ayyubi; Irsalinda, Nursyiva (Proceeding International Conference on Science and Engineering, 2020)
The earthquake is shocks or vibrations in the earth’s surface because of shifting layers of rock at the base of the earth’s surface. This natural phenomenon is common in Indonesia because it lies between Australian, Eurasian, Pacific plates, and it location surrounded by a ring of fire precisely. Therefore, this study aims to cluster earthquake events in Indonesia and describe the characteristics of each group based on clustering results. The method used is the Fuzzy K-Means Clustering. The clustering results obtained from clustering based on the depth, longitude, and latitude. In this study, the data used is the earthquake’s data, which has a magnitude greater than or equal to 5 SR and only clumped by depth. Based on the Davies-Bouldin and Dunn index, the best clustering is 2 clusters which researchers cluster earthquake data in Indonesia into deep and shallow clusters.